Mengukur Peran Job Resources (Supervisor Support, Role Clarity) Sebagai Peredam Dampak Negatif Workload dan Time Pressure Terhadap Employee Perfoemance: Studi pada Bank Rakyat Indonesia Cabang Bangkalan - Muchammad Gusthomi; Ahmad Rizki Sridadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to measure the role of job resources, specifically supervisor support and role clarity, in mitigating the negative impact of workload and time pressure on employee performance at Bank Rakyat Indonesia (BRI) Bangkalan branch. In the face of increasing job demands, heavy workloads and time pressure often hinder optimal performance. Therefore, it is important to understand how job resources can serve as mitigating factors to reduce these negative impacts. This research adopts a quantitative approach with a survey design involving employees of BRI Bangkalan as respondents. Data were collected through questionnaires measuring the variables of workload, time pressure, supervisor support, role clarity, and employee performance. Data analysis was conducted using Structural Equation Modeling (SEM) to test the relationships among the variables. The findings of this study are expected to provide deeper insights into the role of supervisor support and role clarity in enhancing employee performance and offer practical recommendations for BRI management to create a more supportive work environment for employees. This research is also expected to contribute to the development of human resource management theory, particularly in the banking sector.